The Renaissance: a context for the emergence of educational concept 'Training' - Venegas Renauld, María Eugenia (2011)
Greek thought and worldviewChristian, have been die cutting of pedagogical culture of the West. In a historical trace the emergence of the concept "training" as a term pedagogicalcal, the Renaissance is a period that provides evidence to place. In this paper,makes a discussion about analyzing the contribution of some humanists and lexical and contextual conditions that allow hypothesize itsconstruction as such at the time and from the perspective of the concept that is present in García Carrasco and Garcia Dujo